STAT3 Expression and Its Correlation with PD-L1 Expression in Non-Hodgkin’s Lymphoma and Hodgkin’s Lymphoma at Dr. Saiful Anwar Regional Public Hospital in Malang, Indonesian Population - Ailen Oktaviana Hambalie; Eviana Norahmawati; Agustina Tri Endharti; Diah Prabawati Retnani; Nayla Rahmadiani (Advances in Hematology)
Background. Lymphomas are malignant lymphocyte neoplasms that globally account for 10% of cancers in individuals aged <20 years. Malignant lymphomas are divided into Hodgkin’s lymphoma (HL) and non-Hodgkin’s lymphoma (NHL). Despite the availability of many therapeutic modalities for lymphoma, such as Brentuximab vedotin, Nivolumab, and Pembrolizumab, it is still necessary to identify appropriate strategies with minimal side effects. Immunotherapy is a promising approach, exemplified by targeting JAK/STAT3 signaling, which can inhibit tumor growth and enhance antitumor immune responses. Hence, STAT3 (signal transducer and activator of transcription 3) is a promising therapeutic target. PD-L1 (programmed death-ligand 1), an immune checkpoint molecule, is used as a frontline treatment for various cancers. This study aims to determine STAT3 expression and its correlation with PD-L1 expression in NHL and HL to serve as a basis for further research on anti-STAT3 and its combination with other therapy targets. Methods. Samples were obtained from paraffin blocks of patients with confirmed diagnoses of NHL and HL, and then immunohistochemical staining was carried out with PD-L1 and STAT3 antibodies. The collected data were then analyzed using SPSS. Results. Among the 10 HL patients, no patients (0%) expressed STAT3, while nine patients (90%) expressed PD-L1. Among the 10 NHL patients, 1 patient (10%) expressed STAT3, while six patients (60%) expressed PD-L1. There were no significant differences in STAT3 expression and PD-L1 expression between HL patients and NHL patients. There was no correlation between STAT3 and PD-L1 expression in HL and NHL because almost all STAT3 expressions were negative. Conclusion. Although this study revealed no differences between STAT3 and PD-L1 expression in HL and NHL and no significant correlation between STAT3 and PD-L1 expression in HL and NHL, this may serve as the basis for understanding the role of STAT3 and PD-L1 in the regulation of HL and NHL, which may be useful for further research targeting STAT3 and PD-L1 immunotherapy in HL and NHL.